KARAKTERISTIK PEREKAT DAN PEREKATAN TANIN RESORSINOL FORMALDEHIDA PADA SIREKAT AKASIA (Acacia mangium) dan PULAI (Alstonia scholaris): Adhesion and Adhesive Characteristics of Tannins Resorcinol Formaldehyde on Sirekat Acacia (Acacia mangium) and Pulai (Alstonia scholaris) - safni auliarta; Evi Sribudiani; Sonia Somadona (Forestry Faculty of Universitas Hasanuddin, 2021)
The composition of the adhesive content of Tannin Resorcinol Formaldehyde (TRF) is considered more environmentally friendly to use when compared to the phenol resorcinol formaldehyde (RPF) adhesive. In this study to test the strength of the adhesive, acacia (Acacia mangium) and pulai (Alstonia scholaris) were used. This study aims to determine: 1. The characteristics and quality of the adhesive composition of eucalyptus bark tannins, resorcinol and formaldehyde based on SNI 6/4567/1998; and 2. The strength of the gluing composition of eucalyptus bark tannins, resorcinol and formaldehyde on acacia and pulai wood syrup based on SNI 6/6049/1999. The research was conducted using a non-factorial Completely Randomized Design (CRD) consisting of 6 treatments of adhesive composition with 5 repetitions, in order to obtain 30 test samples. The data obtained from the research results were analyzed by means of variance using SPSS 20. Furthermore, if the variance results have a significant effect, further analysis will be carried out using Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results of the research that has been carried out, the six different adhesive compositions produce different values ​​in each treatment, except for treatment P1. P1 has the shape and appearance of a jelly-shaped adhesive so that it cannot be tested and applied to acacia and pulai wood glue. Treatments P2 to P6 can be applied and used for testing and bonding. The pH test and gelatinization test of all treatments were included in SNI 6/4567/1998, the P2 viscosity test did not pass SNI 6/4567/1998. The shear bond strength test was carried out to determine the strength of the adhesive referring to SNI 6/6049/1999, the average value of the best wet shear adhesion test in treatment P6 was 7.89 N/mm2 and the highest average value of shear bonding strength dry on P5 treatment of 26,09 N/mm2.